Class, gender, and sexuality in Thomas Gainsborough's Blue boy - Hedquist, Valerie (London ; New York : Routledge, 2019)
The reception of Thomas Gainsborough's Blue Boy from its origins to its appearances in contemporary visual culture reveals how its popularity was achieved and maintained by diverse audiences and in varied venues. Performative manifestations resulted in contradictory characterizations of the painted youth as an aristocrat or a "regular fellow," as masculine or feminine, or as heterosexual or gay. In private and public spaces where viewers saw the actual painting and where living and rendered replicas circulated, Gainsborough's painting was often the centerpiece where dominant and subordinate classes met, gender identities were enacted, and sexuality was implicitly or overtly expressed.
6 Welcome to AmericaThe Blue Boy on the West Coast; The Blue Boy on Screen and Stage; Notes; 7 Changing Roles for The Blue Boy; The Blue Boy Captivates America; From Manliness to Swish; The Blue Boy in the Comics; Re-appropriating The Blue Boy; Gay Blue Boy; Notes; Conclusion; Bibliography; Index
OCLC-licensed vendor bibliographic record.
Keywords: Gainsborough, Thomas, -- 1727-1788.; Gainsborough, Thomas, -- 1727-1788 -- Criticism and interpretation; ART / History / General; ART / European; SOCIAL SCIENCE / Gender Studies